The Roles of Black Folk? W. E. B. Du Bois's Peace Advocacy and Its Legacy. Issue 3 (2nd October 2022) - Lieberman, Robbie
Abstract: This essay highlights W. E. B. Du Bois's peace advocacy, encouraging readers to consider "the roles of Black folk" in affecting U.S. foreign policy. It contextualizes the U.S. Department of Justice's 1951 indictment of Du Bois, the occasion for his writing In Battle for Peace . The essay's chief concern is the effects, both short and long term, of the anticommunist attacks on Du Bois and his contemporaries. Du Bois's peace advocacy drew harsh attacks from those who supported U.S. Cold War policies or who worried about being associated with communism if they championed peaceful coexistence with the Soviet Union. Moreover, his Cold War activism and writing have received less attention than his earlier contributions to American life and letters. Yet Du Bois linked his peace efforts to Black liberation and socialism, and the ideas he spoke and wrote about during the latter part of his life continue to have significant implications for our own time.